Hodgkin's Disease - Darfioes Basir; Inda D. Arif; Moeslichan S. (Paediatrica Indonesiana, 1978)
A case of Hodgkin's disease in an 8-year-old Indonesian boy is presented. The treatment was stanted 2Â½ years after the first onset of the symptoms,consisting of vincristine, cyclophosphamide and prednisone. It seemed that this combination gave good results; after 12 weeks of treatment the lymphnodes disappeared and no new swellings developed. Despite the good results, continuous observation is necessary.